Alternative Tendon Coaptations to the Pulvertaft Weave Technique: A Systematic Review and Meta-Analysis of Biomechanical Studies. (May 2023) - Graham, Emily M.; Oliver, Jeremie D.; Hendrycks, Russell; Maglic, Dino; Mendenhall, Shaun D.
Background: The Pulvertaft weave technique (PT) is frequently used during tendon repairs and transfers. However, this technique is associated with limitations. In this systematic review and meta-analysis, quantitative and qualitative analyses were performed on in vitro, biomechanical studies that compared the PT with alternative techniques. Methods: Articles included for qualitative and/or qualitative analysis were identified following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies included in the meta-analysis were analyzed either as continuous data with inverse variance and random effects or as dichotomous data using a Mantel-Haenszel analysis assuming random effects to calculate an odds ratio. Results: A comprehensive electronic search yielded 8 studies meeting inclusion criteria for meta-analysis. Two studies with a total of 65 tendon coaptations demonstrated no significant difference in strength between the PT and traditional side-to-side (STS) techniques ( P = .92). Two studies with a total of 43 tendon coaptations showed that the STS with 1 weave has a higher yield strength than the PT ( P = .03). Two studies with a total of 62 tendon repairs demonstrated no significant difference in strength between the PT and the step-cut (SC) techniques ( P = .70). The final 2 studies included 46 tendon repairs and demonstrated that the wrap around (WA) technique has a higher yield strength than the PT ( P < .001). Conclusions: The STS, SC, and WA techniques are preferred for improving tendon form. The STS and WA techniques have superior yield strengths than the PT, and the SC technique withstands similar stress to failure as the PT.